2019
DOI: 10.3390/jcdd6040036
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Mutations and Rheumatic Heart Diseases

Abstract: Acute rheumatic fever (ARF) is an autoimmune disease affecting the heart-valve endocardium in its final stage. Although rare in developing countries, ARF persists in third-world countries, particularly Senegal, where rheumatic heart diseases (RHDs) are the most common pediatric cardiovascular pathology. This study aimed to investigate mutations in MT-CYB in ARF and RHD in Senegalese patients. MT-CYB was amplified from blood samples from ARF patients at the Clinical of Thoracic and Cardiovascular Surgery of Fan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The first original article investigated MT-CYB mutations in acute rheumatic fever and rheumatic heart diseases among Senegalese patients. The authors of this study found a narrow link between MT-CYB mutations and acute rheumatic fever and its complications, i.e., rheumatic heart diseases [ 7 ]. In the second original study, conducted in Uruguay on two separate cohorts (children, n = 682; adolescents, n = 340), the authors tested potential associations between anthropometric parameters (i.e., weight, height and body mass index (BMI)) in early life stages and the state of the cardiovascular system in early childhood at the beginning of adulthood [ 8 ].…”
mentioning
confidence: 99%
“…The first original article investigated MT-CYB mutations in acute rheumatic fever and rheumatic heart diseases among Senegalese patients. The authors of this study found a narrow link between MT-CYB mutations and acute rheumatic fever and its complications, i.e., rheumatic heart diseases [ 7 ]. In the second original study, conducted in Uruguay on two separate cohorts (children, n = 682; adolescents, n = 340), the authors tested potential associations between anthropometric parameters (i.e., weight, height and body mass index (BMI)) in early life stages and the state of the cardiovascular system in early childhood at the beginning of adulthood [ 8 ].…”
mentioning
confidence: 99%